Adopting social health insurance in Nepal: A mixed study - Paneru, Damaru Prasad; Adhikari, Chiranjivi; Poudel, Sujan; Adhikari, Lal Mani; Neupane, Deepak; Bajracharya, Juli; Jnawali, Kalpana; Chapain, Kamal Prasad; Paudel, Nabaraj; Baidhya, Nirdesh; Rawal, Ashok (Frontiers in Public Health, 2022)
Objective: The Social Health Insurance Program (SHIP) shares a major portion of social security, and is key to the Universal Health Coverage (UHC) and health equity. The Nepal government initiated it in the fiscal year 2015/16 in three districts, on the principle of financial risk protection. Furthermore, adoption of the program depends on the stakeholders’ behaviors, mainly, the beneficiaries’ and the providers’. Therefore, we aimed to explore and assess their perception and experiences regarding various factors acting on SHIP enrolment and adherence. Methods: A cross-sectional, facility-based, concurrent mixed-method study was carried out in Kailali, Baglung, and Ilam districts, with 822 beneficiaries, sampled using the PPS, attending health care institutions, for quantitative data. Similarly, seven focus group discussions (FGDs) and 12 in-depth interviews (IDIs) were conducted with beneficiaries and service providers. Manual thematic analysis with predefined themes, was carried out for qualitative data. Percent, frequency, mean, and median were used to describe the variables, and the chi-square test and binary logistic regression were used to infer the results. We then combined the qualitative data from beneficiaries’ and providers’ perception, and experiences to explore different aspects of health insurance programs as well as to justify the quantitative findings. Results and prospects: Of a total 822 respondents (insured- 404, uninsured- 418), 370 (45%) were male. Families’ median income was USD 65.96 (8.30 290.43). Insurance premium Perception did not differ between the insured and uninsured groups (p=.53). Similarly, service utilization (OR=220.4; 95% CI, 123.3-393.9) and accessibility (OR=74.4; 95% CI, 42.5-130.6) were found to have high odds among the insured as compared to the uninsured respondents. Qualitative findings showed that the coverage and the service quality were poor. Enrolment was gaining momentum despite a one-tenth dropout rate. Moreover, different aspects, including provider-beneficiary communication, benefit packages, barriers, and ways to go, are discussed. Additionally, we also argue for some alternative health insurance schemes and strategies that may have possible implications in Nepalese contexts. Conclusions: Although enrolment is encouraging, adherence is weak, with a low dropout rate and poor renewal. Patient management strategies and insurance education are recommended urgently. Further, some alternate schemes and strategies may be considered.